Attitude of Staff Nurses Toward Hospital Information System in Nursing Practice at a Selected Tertiary Hospital in Malolos, Bulacan, Philippines - Eusebio, Jonell L.; Cabanatan, Andrea Nica A.; Manaloto, Allan M.; Cuevas, Joseph Erol T.; Gernalin, Edward C.; Cruz, Rheasol U.; Capeding III, Mauricio S. (International Journal of Computing Sciences Research, 2023)
Purpose – It is evident that the nursing profession is being impacted by the rising usage of computer technology in the healthcare settings. This study aimed to identify the attitude of staff nurses toward Hospital Information System in nursing practice in a selected hospital in Malolos, Bulacan. Method – This research utilized a descriptive-correlational design and 50 staff nurses responded using total population sampling method. The attitude of staff nurses toward computers in healthcare was measured using the P.A.T.C.H. (Pretest for Attitudes Toward Computers in Healthcare) Assessment Scale v. 3. Spearman correlation test was used to determine the relationship between the variables. Results – This study confirmed that there was a significant relationship (Rs = 0.280, p = 0.040) between the educational attainment of staff nurses and their attitude toward computer applications in nursing practice. As educational attainment increased, so did the positive attitude toward using computer applications in nursing practice. However, there was no significant relationship between Gender (Rs = -0.015, p = 0.913), Age (Rs = -0.083, p = 0.549), Marital Status (Rs = 0.042, p = 0.761), and Computer Experience (Rs = 0.196, p = 0.156) of the staff nurses and their attitude toward computer application in nursing practice at 0.05 level of significance. Conclusion – These findings underscored the importance of educational background in shaping nurses’ attitudes and their preparedness to adopt computer technologies in their practice. Recommendations – This suggested a need for more significant investment in educational programs that focus on computer literacy and technology integration in nursing practice. Research Implications – To gain a more comprehensive understanding, further research could investigate additional factors that may influence attitudes toward computer applications in nursing practice.